M-ary phase modulation for digital watermarking - Xin, Yongqing; Pawlak, Mirosław (Zielona Góra: Uniwersytet Zielonogórski)
In spread spectrum based watermarking schemes, it is a challenging task to embed multiple bits of information into the host signal. M-ary modulation has been proposed as an effective approach to multibit watermarking. It has been proved that an M-ary modulation based watermarking system outperforms significantly a binary modulation based watermarking system.
Keywords: multibit watermarking; M-ary phase modulation; watermark robustness; data capacity